2011
DOI: 10.1016/j.cca.2010.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of modification sites formed on human serum albumin at various stages of glycation

Abstract: Background-Many of the complications encountered during diabetes can be linked to the nonenzymatic glycation of proteins, including human serum albumin (HSA). However, there is little information regarding how the glycation pattern of HSA changes as the total extent of glycation is varied. The goal of this study was to identify and conduct a semi-quantitative comparison of the glycation products on HSA that are produced in the presence of various levels of glycation.Methods-Three glycated HSA samples were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 52 publications
7
106
2
1
Order By: Relevance
“…This seemingly novel adduct is attributed tentatively to a somewhat rare, nonenzymic, posttranslational modification occurring in vivo by the slow reaction of HSA with glucuronic acid in plasma (Mazzuchin et al, 1971;Smith et al, 1990). In a separate study using similar analytical methods, we found glucosylated Lys525 (Barnaby et al, 2011) in vivo (data not shown). Neither glucuronylated Lys525 nor any of the N-acylations and glycations associable with either diclofenac AG or reactive thioester metabolites of diclofenac were found on HSA isolated from the three control subjects.…”
Section: Circulating Protein Adducts In Diclofenac Patientsmentioning
confidence: 90%
See 1 more Smart Citation
“…This seemingly novel adduct is attributed tentatively to a somewhat rare, nonenzymic, posttranslational modification occurring in vivo by the slow reaction of HSA with glucuronic acid in plasma (Mazzuchin et al, 1971;Smith et al, 1990). In a separate study using similar analytical methods, we found glucosylated Lys525 (Barnaby et al, 2011) in vivo (data not shown). Neither glucuronylated Lys525 nor any of the N-acylations and glycations associable with either diclofenac AG or reactive thioester metabolites of diclofenac were found on HSA isolated from the three control subjects.…”
Section: Circulating Protein Adducts In Diclofenac Patientsmentioning
confidence: 90%
“…Lys414, in HSA site 2, diclofenac's high-affinity binding site (Chamouard et al, 1985), is modified by the cyclic imide but not by diclofenac AG or benzylpenicillin. Lys199 and Lys414, but neither Lys195 nor Lys432, are glycated spontaneously by glucose (Barnaby et al, 2011) via the same pathway of reversible imine formation and slow, cumulative, Amadori rearrangement. Diclofenac AG glycations were identified notwithstanding incubations did not contain cyanoborohydride, which reduces imines and enhances binding of AG, including diclofenac AG (Kenny et al, 2004), to HSA (Smith et al, 1990).…”
Section: Circulating Protein Adducts In Diclofenac Patientsmentioning
confidence: 99%
“…1). The total amount of such accumulated products is known to be dependent on the type of sugar that is causing the glycation, the incubation time and sugar concentration, as well as the type protein that is being modified (Barnaby et al, 2011). The first product of Maillard reaction is a simple glycosylamine, which readily undergoes the Amadori rearrangement to produce 1-amino-1-deoxy-2-ketoses.…”
Section: Hyperglycaemia -The Basic Knowledge On Louis Maillard's Discmentioning
confidence: 99%
“…Albumin is one of the main circulating proteins which undergoes glycation due to its abundance in serum (35 g/l), long half-life (21 days) and presence of multiple glycation sites (Barnaby et al 2011). Glycation induced modifications have a detrimental impact on albumin structure as its-1) conformation changes, (Rondeau and Bourdon 2011) 2) free thiols gets oxidized to disulfide linkages or thiol radicals (S-S or S, respectively) (Bourdon et al 1999), 3) initially globular albumin refolds into amyloid fibrils comprising cross-β structure (the β aggregates specifically bind to amyloid specific dyes-Congo red and thioflavin T (Th T) (Bouma et al 2003).…”
Section: Introductionmentioning
confidence: 99%